2008
DOI: 10.1098/rsta.2008.0023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surfactant on the multiscale structure of bubbly flows

Abstract: It is well known that a bubble in contaminated water rises much slower than one in purified water, and the rising velocity in a contaminated system can be less than half that in a purified system. This phenomenon is explained by the so-called Marangoni effect caused by surfactant adsorption on the bubble surface. In other words, while a bubble is rising, there exists a surface concentration distribution of surfactant along the bubble surface because the adsorbed surfactant is swept off from the front part and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 29 publications
4
55
0
1
Order By: Relevance
“…Under these conditions, an increase in T c , reduces the viscosity and weakly promotes turbulence; this promotes collision and increases film drainage speed and thus, coalescence. Grover et al [78] [13][14][15][16][17][18] ) observed the same decrease in the homogeneous flow regime, but no effect in the heterogeneous flow regime. Yang et al [190] (d c = 0.041 m, H 2 , CO/Paraffin) observed a decrease in ε G with an increase in both T c (293-523 K) and p c (1-3 MPa).…”
Section: Temperaturementioning
confidence: 65%
See 1 more Smart Citation
“…Under these conditions, an increase in T c , reduces the viscosity and weakly promotes turbulence; this promotes collision and increases film drainage speed and thus, coalescence. Grover et al [78] [13][14][15][16][17][18] ) observed the same decrease in the homogeneous flow regime, but no effect in the heterogeneous flow regime. Yang et al [190] (d c = 0.041 m, H 2 , CO/Paraffin) observed a decrease in ε G with an increase in both T c (293-523 K) and p c (1-3 MPa).…”
Section: Temperaturementioning
confidence: 65%
“…Conversely, if "non-coalescing" solutions are employed, the transition flow regime is identified by the appearance of "clusters of bubbles", as defined in refs. [15,16] and observed by [7]. The flow regime transitions from the homogeneous flow regime towards the transition flow regime concept are displayed in Figure 3.…”
Section: The Flow Regimes In Bubble Columnsmentioning
confidence: 99%
“…The model of elastic collision among contacting bubbles, which is derived under the potential flow assumption, results in a formation of horizontal bubble clusters (Sangani and Didwania, 1993;Smereka, 1993). The horizontal clusters are observed experimentally (Zenit et al, 2001;Figueroa-Espinoza and Zenit, 2005;Takagi et al, 2008) by adding a small amount of electrolyte or surfactant in order to reduce the bubble coalescence. In the usual bubble column, however, coalescence frequency occurs.…”
Section: Introductionmentioning
confidence: 99%
“…気泡流には様々なスケールがあり、気泡が生成 する乱れは多くの研究者の注目を集めている。そ の乱れは、流れ場と相互作用し、単相流とは異な る複雑な流動構造を示す [1][2][3][4][5][6]。特に気泡クラスタ ーは、乱流の秩序渦構造よりも大きく、大規模な 流動構造そのものを変化させる [7,8]。 そのため気 泡クラスター形成の有無について様々な報告が 行われている [9][10][11]。 気泡のクラスター形成は、まず理論的に予測さ れた。ポテンシャル流れを仮定し、複数の気泡が 上昇する際、気泡間相互作用によって水平面に気 泡 が クラスターを 形成することが報告された [12,13]。一方で、実際の気泡流では、気泡同士の 合体によって気泡径差が生まれ、通常気泡のクラ スター構造は観察されない。さらに前述のポテン シャル流れを用いた理論でも、気泡径差を考慮す るとクラスターは形成されない [14]。しかし、実 験的研究において、界面活性剤や電解質を混入さ せることで気泡クラスターの形成が報告されて いる [15,16]。 界面活性剤や電解質の混入は、気泡表面の境界 条件を大きく変化させる。界面活性剤では気泡の 抗力の増加や合体を防ぎ、電解質ではやクリーン な気泡を保ちながら気泡合体を防ぐ [17][18][19][20] /01 02 0/%/ü ! 1 ö 3 4 5 6 7 8 9 6 % !ú ÷ ù ' ü ü ö !…”
Section: 緒 言unclassified